2020
DOI: 10.1126/scitranslmed.abc0441
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal synthetic epithelial linings

Abstract: Epithelial tissues line the organs of the body, providing an initial protective barrier as well as a surface for nutrient and drug absorption. Here, we identified enzymatic components present in the gastrointestinal epithelium that can serve as selective means for tissue-directed polymerization. We focused on the small intestine, given its role in drug and nutrient absorption and identified catalase as an essential enzyme with the potential to catalyze polymerization and growth of synthetic biomaterial layers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 65 publications
(90 reference statements)
0
44
0
Order By: Relevance
“…To overcome these obstacles, approaches such as chemical modifications and nano/microcarriers, gastrointestinal injectors are developed. [8][9][10][11][12] Despite the advancements, the viscous digestive juices may hinder effective diffusion of the modified drugs and drug carriers, and the large-sized gastrointestinal injectors may block the digestive tract. The presented microneedle robots can well solve these issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these obstacles, approaches such as chemical modifications and nano/microcarriers, gastrointestinal injectors are developed. [8][9][10][11][12] Despite the advancements, the viscous digestive juices may hinder effective diffusion of the modified drugs and drug carriers, and the large-sized gastrointestinal injectors may block the digestive tract. The presented microneedle robots can well solve these issues.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1–5 ] Whereas, due to the complex physiological environments of gastrointestinal tracts, such as the abundant digestive enzymes, the spatio‐temporal varying pH values, and the mucosal barriers, many drugs are easily inactivated and have low absorption rates, especially macromolecules like proteins. [ 6,7 ] Thus, special chemical modifications and nanocarriers are introduced to oral drug delivery systems to overcome the biological barriers, [ 8–10 ] and physical devices based on mechanical forces are developed to realize gastrointestinal injections. [ 11,12 ] Despite the progress, it remains controversial whether these modified drugs and drug carriers can effectively diffuse through viscous digestive juices to the action sites.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the reactivity of the chemical residues in the PDA structure toward nucleophilic amines and thiols yields a superior capacity for immobilizing and conjugating a variety of molecules through Michael addition and Schiff base formations (Yang et al, 2014 ). DNA, drugs, cells, minerals, peptides, and proteins have been functionalized on PDA-modified substrates for diverse TE applications (Ryu et al, 2010 ; Tsai et al, 2014 ; Cheng et al, 2019 ; Li et al, 2020 ; Rühs et al, 2020 ). It has been reported that PDA can promote cell adhesion to various substrates (Ku and Park, 2010 ).…”
Section: Scaffold Main Characteristicsmentioning
confidence: 99%
“…In this context, immense efforts have been dedicated to expedite the process of PDA to nanoparticle formation equilibrium, substrate coating, or matrix crosslinking. These steps are thus critical performance indicators in this field [31–36] . Somewhat surprisingly, a counterintuitive method that retards the polymerization of dopamine into PDA rather than accelerates it is rarely investigated.…”
Section: Figurementioning
confidence: 99%